Angioleiomyosarcoma of mamma. Presentation of a case. - Lidia Torres Ajá (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2006)
Here is presented a case of a 65 year old female patient, resident of Palmira municipality, Cienfuegos, who was treated in the Universitary Hospital ¨Dr. Gustavo Aldereguia Lima¨, with a 5 cm tumour in the left mama. A total mastectomy of Maden was applied at the time of being classified such a tumour by the Pathologic Anatomy Department of the before mentioned centre, as an angioleiomyosarcoma. In the 25 years of existence of this hospital, this is the first case of a mammal angioleiomyosarcoma detected, so we consider it a case of scientific interest and decided to publish it.